Screening of effective microscopic fungi that contribute to the improvement of plant growth and development (Eurasian Journal of Ecology, 2022)
Modern technologies used in agriculture are mainly based on the use of chemical plant protection products, which inevitably leads to contamination of manufactured products and the environment. In this regard, the development and application of environmentally safe biological products based on the use of microorganisms that improve the growth and development of plants is an urgent task of modern crop production.Currently, microorganisms with a set of beneficial properties for plants are commonly referred to as PGPM (from Plant Growth-Promoting Microorganisms – microorganisms that promote plant growth). Studies of this promising group of microorganisms for practical use are of great interest. Among the PGPs of various taxonomic groups, a wide range of useful properties for plants are distinguished by micromycetes. They are potential objects of agrobiotechnology for the development of biological plant protection products against phytopathogens, as well as biological products that stimulate growth and increase plant productivity.The article presents data on the selection of strains of micromycetes isolated from agrocenoses of grain and feed crops of Kazakhstan that improve plant growth and have the ability to increase the availability of nutrients for them. Because of the screening, out of 44 strains, 2 were selected that showed the greatest activity and had several valuable properties at once.The selected effective micromycetes had a positive effect on the physiological processes of plants (morphometric parameters and photosynthesis), as well as increased the availability of nutrients (phosphorus and potassium).Key words: potassium solubilization, micromycetes, growth-stimulating activity, phosphatmobilization.